Real-time mastitis detection in livestock using deep learning and machine learning leveraging edge devices - Ghosh, Kawshik Kumar; Islam, MD.Fahim-Ul; Efaz, Abrar Ahsan; Ratul, Md. Wahid Sadiq; Shatil, Md Zaid Hassan Khan (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.